Profile of Students’ Reasoning in Solving Geometry Problems (Plane Figures) at Jejahitan Bali: A Gender-Based Analysis at Widyalaya High School in Palu - Ni Kadek Novitasari; Sukayasa Sukayasa; Pathudin Pathudin (FKIP - Universitas Riau, 2026)
This study aims to obtain a description of students' reasoning profiles in solving geometric problems (flat shapes) in Balinese sewing reviewed from the perspective of gender differences at Widyalaya High School Palu. This research is descriptive with a qualitative approach. The subjects were 1 male and 1 female students from Hindu schools. Data collection techniques use observation and interview techniques. Data analysis techniques include data collection, condensation, presentation, and verification of conclusions. Validity test by conducting time triangulation. The results of this study show: (1) male subjects, after making Balinese sewing, were able to identify that in the Balinese ituk-ituk sewing there were triangular elements in it, in the Balinese taledan sewing there were rectangular elements and in the Balinese tamiang sewing there were circular elements. (2) Female subjects identified in more detail the Balinese ituk-ituk stitching, mentioning the characteristics of a triangular flat shape, in the taledan stitching the subject mentioned the characteristics of a rectangular flat shape and in the Balinese tamiang stitching the base has the characteristics of a circular flat shape.